NDT of composite laminates using phased-array ultrasonic technnique - Shah Utkarsh Ketan (2017)
Several commercial engineering components in aerospace, ship building, sports industry are made of composite materials replacing conventional composite laminates necessitating issues of defect detection in them during either manufacturing or maintenance. Phased Array Ultrasonic Technique (PAUT) is emerging non-destructive technique (NDT) which enable rapid scanning of component s and also provide more accurate results than the conventional ultrasonic testing. Industrial emphasis on eco no mic s and safety, it is critical to use and develop robust and practical NDT methods. In this stud y, ultrasonic C-scan technique is used to detect various artificial defects using a 5MHz phased array wheel probe in laminated composite plate s. The artificial defects with varying shapes and sizes made of polymer film s were embedded in the testing composite laminates at different layers and position. Both unidirectional glass fibre reinforced epoxy polymer (GFRP) and car bon fibre reinforced epoxy polymer (CFRP) composite laminates were examined using portable Doppler PA instrument PH ASCAN®. Special tu1in g and optimization techniques including different element combination and focus settings and distance amplitude correction (DAC) were use d to reduce noises and to achieve better image re solution. The C-scan measurement is in good agreement with the actual size and position of defect s: quantifying the size and location of defect s. In addition, the attenuation factors in both materials were measured. It was found that the noise to signal ratio in CFRP laminates is much lower than GFRP laminates, which resulted in better C-scan image. The stud y also includes the detection of flaw areas for the composite laminates impacted under different load s. Also the feasibility of roller type transducer to detect the flaw s in curved surfaces is demonstrated. Finite element modelling was also carried out on the laminate structure to understand the interaction of defect s with the waves using commercial finite element software ABAQUS ® CAE.